Collaborative Governance In The Development Of The Potential Of The Marine Natural Tourism Park Of Seventeen Riung Islands, Ngada Regency, East Nusa Tenggara - Itu, Maria Trivonia; Marsitadewi, Komang Ema; Suryawan, Dewa Ketut (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
The Marine Nature Tourism Park (TWAL) of Riung Seventeenth Island in Ngada Regency is a conservation area with excellent development potential. However, its management has various challenges, such as suboptimal coordination between stakeholders, lack of communication between stakeholders, less effective feedback, lack of openness to build trust, and lack of creativity in dealing with the problems. Seeing this phenomenon, collaboration between parties is needed to optimize the development of TWAL. This study aims to determine the role of stakeholders and the collaborative process in the development of TWAL. This study uses a descriptive qualitative approach with data collection methods through in-depth interviews, field observations, and documentation studies. The results show that the collaboration has involved stakeholders from the government sector (BKSDA NTT, Fisheries and Marine Service, Tourism Office, and village government), the private sector (lodging and restaurant entrepreneurs), local communities (fishermen and seaweed farmer groups), and NGOs (Komodo Survival Program). The role of stakeholders is relatively straightforward, but the implementation of collaboration is still not optimal. Inhibiting factors include overlapping authority, lack of formal regulation, and promotion that has not been maximized. In the aspect of initial conditions, it was found that there was a lack of resources, damaged infrastructure, and waste management that had not been integrated. Facilitative leadership by BKSDA NTT has succeeded in increasing community participation and building trust through preventive approaches and participatory dialogue. The institutional design shows informal cooperation across sectors, but a strong legal basis does not entirely support it. In the collaborative process, stakeholders are involved in regular meetings, training, and coordination, although there are still gaps in active engagement and digital communication due to network constraints. The collaboration results show increased tourist visits, public awareness of environmental conservation, and contribution to the local economy. However, there is still a need to strengthen coordination and cross-agency policies.